Lifestyle Migration and Colonial Traces in Malaysia and Panama - Benson, Michaela (Migration, Diasporas and Citizenship,, 2018)
Leading scholars in the sociology of migration, Michaela Benson and Karen O'Reilly, re-theorise lifestyle migration through a sustained focus on postcolonialism at its intersections with neoliberalism. This book provides an in-depth analysis of the interplay of colonial traces and neoliberal presents, the relationship between residential tourism and economic development, and the governance and regulation of lifestyle migration. Drawing on ethnographic fieldwork undertaken by the authors among lifestyle migrants in Malaysia and Panama, they reveal the structural and material conditions that support migration and how these are embodied by migrant subjects, while also highlighting their agency within this process. This rigorous work marks an important contribution to emerging debates surrounding privileged migration and mobility. It will appeal to sociologists, social theorists, human and cultural geographers, economists, social psychologists, demographers, social anthropologists, tourism and migration studies specialists.